Nepal needs Continuing Professional Development for Re-registration in Nursing and Midwifery - Simkhada, Bibha; van Teijlingen, Edwin; Sharma, Chandrakala; Pandey, Apsara; Simkhada, Padam (Journal of Nepal Health Research Council, 2024)
The nursing and midwifery profession needs to stay up to date with the latest developments. In this Viewpoint, we shall be referring to ‘nurses’ and ‘nursing’ to mean ‘nurses and midwives’ and ‘nursing and midwifery’ respectively. Nurses must continue to update their skills and competences to meet changing future population health needs effectively and safely. However, the reality is that many staff are reporting difficulty accessing and completing Continuing Professional Development (CPD) in all settings. Keywords: CPD; midwifery; nursing; post-registration education; training.